KONSEP PENDIDIKAN BERKELUARGA DALAM KITAB ‘UQUDULLIJAIN RELEVANSINYA DENGAN PENDIDIKAN ISLAM DI INDONESIA - Muqo robin (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
This study is an attempt to know (1) biography of the author of the book 'Uqudullijain. (2) the attitude of Nawawi in the book 'Uqudullijain. (3) Relevancy of the concept of family in the book 'Uqudullijain with Islamic education in Indonesia. This study use induction and deductive method to analyze the data. The research findings indicate that family education in the book "Uqudullijain offered Nawawi have relevance in his day, is not relevant when applied to contemporary and necessary to adjust in order to remain relevant. While the answer to the above question is in accordance with the results of the study are as follows: (1) Nawawi’s thought is said to be very traditionalist, it is influenced by the time she concocted since 114 years ago, so the method used and culture the current was very supportive of Nawawi to pour the thought that is traditionalist. (2) Nawawi’s attitude look too superiorized to male and curb the rights and degrading women, but there is little his opinion that respects women. He was also seen in interpreting a verse of the Koran textually different from the contextual contemporary interpreters. (3) the book 'Uqudullijain was relevant at the time of authorship, but because times are kept so the advance then it is possible a content of the book is irrelevant, so that should do reshuffle and adjustment, in order to keep abreast of the Age and the demands of human needs.